Increasing Age Is Associated with Worse Prognostic Factors and Increased Distant Recurrences despite Fewer Sentinel Lymph Node Positives in Melanoma. (18th March 2012) - Page, A. J.; Li, A.; Hestley, A.; Murray, D.; Carlson, G. W.; Delman, K. A.
Abstract : Background . Advanced age is associated with a poorer prognosis in patients with melanoma. Despite this established finding, a decreased incidence of positive sentinel lymph nodes (SLNs) with advancing age has paradoxically been described. Methods . Using a single-institution database of melanoma patients between 1994 and 2009, the relationship between standard clinicopathologic variables and recurrence based on age was evaluated. Results . 1244 patients who underwent successful SLN biopsies were analyzed (mean followup 80.3 months). Increasing age was independently associated with worse survival on multivariable analysis (P = 0.02 ). SLN status was more likely to be negative if the patient was older (P = 0.01 ). Conclusions . Our data supports the paradox that increasing age is associated with a lower frequency of positive-SLN biopsies despite age itself being a poor prognostic factor. We propose that age-dependent variations in the primary tumor and the patient may predispose to a hematogenous route of spread for the older population, leading to worse survival.